Nursing Care in Diabetes Mellitus Type-2 in The Bougenvil Room of The General Hospital dr. H. Koesnadi Bondowoso Indonesia: Case Report - Hamidah Retno Wardani; Leni Agustin; Danang Prasetyo; Elok Faiqotul Himmah (KHD Production, 2024)
Diabetes mellitus is a disease caused by the body being unable to release or use insulin adequately so that glucose levels in the blood are high. If this high blood glucose level lasts for a long time, there will be a disturbance in the alcohol metabolic pathway which results in increased sorbitol production so that various nursing problems arise, including ineffective peripheral perfusion. This study uses a case study method in the form of exposure to the results of applying the client's nursing care process in accordance with the theory, containing a discussion of nursing actions that occur in the field. This research was conducted on one client who experienced Diabetes mellitus for 4 visits starting from May 15, 2023, through data collection of interviews, observations, physical examinations, and documentation studies. The results of this study were obtained from the assessment, namely Ineffective Peripheral Perfusion in accordance with the theory, and diagnosis as in accordance with the client's condition, while the implementation refers to the interventions that have been set, and the evaluation refers to the general objectives and specific objectives that have been set in accordance with the theory.